MITIGASI COVID-19 MELALUI KONTEN KREATIF DI MEDIA SOSIAL - Saefuddin Saefuddin; La Ode Santiaji Bande; Hasmina Tari Mokui (Journal Publicuho, 2021)
This Thematic Real Work Integrated with Community Service aims to increase the literacy of the people of Southeast Sulawesi regarding COVID-19 and how to mitigate it by using creative content media. This thematic program is one form of community service, so that its implementation follow the action research method with 5 (five) stages, i.e. (1) Diagnosis; (2) Planning; (3) Implementation; (4) Evaluation; and (5) Special learning. This thematic program was attended by 22 students under supervision of three field lecturers and lasted for 30 days online. During this program, more than 20 posters/e-cards and 30 videos have been produced. The content has been disseminated on various social media through the accounts of students and supervisors as well as other internet media. Based on the results of creative content in the form of posters, the public can improve their literacy on social and physical distancing as an effort to accelerate COVID-19 mitigation. Meanwhile, creative content in the form of videos can train the public on how to use and prepare their own hand sanitizer, masks, and PPE by utilizing materials found around them. Thus, it can be concluded that this thematic program has succeeded in providing guidance and debriefing to the people of Southeast Sulawesi as a mitigation effort against the COVID-19 outbreak.